Early Undifferentiated Spondyloarthropathy in a Patient with Sarcoidosis - Murat KARA,; Levent ÖZÇAKAR,; Fuat KALYONCU,; Ayşen AKINCI2, (Archives of Rheumatology, 2013)
In this article, we present a 49-year-old male case who was admitted with inflammatory back pain and uveitis when he was in remission for sarcoidosis. The concomitance of undifferentiated spondyloarthropathy and sarcoidosis with an emphasis on their possible etiological association was also discussed in the light of current diagnostic and therapeutic challenges.